Pengaruh Customer Experience, Perceived Quality, dan Price Terhadap Brand Loyalty dengan Variable Mediasi Customer Satisfaction pada Smartphone Iphone : Studi Kasus pada Pengguna iPhone di Semarang - Cahya Faridatul Umami; Ika Indriasari; Rr. Hawik Ervina I (Global Leadership Organizational Research in Management, 2025)
The tight competition in the premium smartphone industry requires companies to understand the factors that influence brand loyalty. iPhone is one of the products that remains in demand despite its relatively high price, indicating the important role of customer experience and perceived quality. This study aims to examine the effect of customer experience, perceived quality, and price on brand loyalty with customer satisfaction as a mediating variable. This research approach is quantitative with a survey method of 100 iPhone user respondents in Semarang City. Data analysis was carried out using the Structural Equation Modeling (SEM) technique with the help of the SmartPLS application. The results of the study indicate that customer experience, perceived quality, and price have a positive and significant effect on customer satisfaction. Furthermore, customer experience, perceived quality, and price do not affect brand loyalty. However, customer satisfaction has a positive and significant effect on brand loyalty. Then, customer satisfaction is able to mediate the relationship between customer experience and brand loyalty. However, customer satisfaction is unable to mediate the relationship between perceived quality and price on brand loyalty. The practical implication of these results is the importance of companies to focus on improving customer experience, product quality, and pricing strategies in order to strengthen their brand position in a competitive market.